The development of SightHeart: a gamified serious game training tool for analytical skills and values internalization - Meor Zamari, Wan Nurul Nazirah; Mohd Ayub, Ahmad Fauzi (Human Resource Management Academic Research Society, 2017)
This paper addresses the development of a two-dimensional (2D) computer serious game prototype named SightHeart as an alternative informal tool for training students’ analytical skills and values internalization. The prototype was developed using an extension of the ADDIE model called DGBL-ID and was evaluated based on users’ motivation, engagement, acceptance and behaviour intention towards the serious game. The study aims to highlight on developmental issues related to serious games such as lack of entertainment value due to heavily-focused on the learning content. Simultaneously, the game also intends to address learning issues among undergraduate students reported by literature, particularly the lack of critical thinking skills and having poor character that may affect their employability. The concept of gamification, motivation, psychological and other related learning theories were used as a combined approach to overcome these issues to boost their motivation and engagement towards SightHeart. Results suggested that SightHeart is successful in terms of positive influence over users’ attitudes and their perceived learning opportunities, which contributed to students’ better acceptance towards serious games.